What's so funny about God? : a theological look at humor - Wilkens, Steve, 1955- (IVP Academic, an imprint of InterVarsity Press, 2019)
"Jokes often touch on the biggest topics of our existence, but many Christians haven't taken humor seriously. This insightful yet delightful crash course from philosopher Steve Wilkens argues that viewing Scripture and theology through the lens of humor helps us understand the gospel and avoid the pitfalls of both naturalism and gnosticism, while facilitating a humble, honest, and appealing approach to faith"--